Scribbling Refinement vis-à-vis Scribbling Attainment of the First Year Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper ushers to ascertain the scribbling refinement status of the 36 first year students of Bachelor of Science in Hospitality Management of Isabela State University, San Mariano Campus, Isabela Philippines enrolled during the SY 2019-2020 who finished the Senior High School program. The data gathered were deeply analyzed through frequency count, percentage and ranking. The conspicuous findings are, first, out of the 36 students, 24 of them exemplified poor understanding of the topic given resulted into confusion which was denoted in their outputs. Second, the level of scribbling refinement on the organization of ideas, majority of the participants had fairly organization of idea and development with no supporting details and lastly, on the level of scribbling attainment when it comes into protocols, most of the  participants’ outputs were marked with numerous errors in grammar, usage which imperatively restrained with the meaning of the outputs. In relation to respondents’ level of writing difficulties on writing style, most of them had serious and frequent problems with word choice and sentence structure.